Sustainability analytics toolkit for practitioners creating value in the 21st century - Siew, Renard
"This book solicits meaningful contributions from key experts and practitioners that have been dealing with the emerging area of sustainability analytics. In doing so, readers would understand the cost, impact and performance of their sustainability initiatives. The book covers current analytical tools (eg: frameworks, standards, ESG indexes) to measure sustainability, and how these tools embed the Sustainable Development Goals (SDGs). In addition to that, a part of the book is also dedicated to the application of sustainability analytics, highlighting key challenges as well as the importance of engagement and communication in shaping the future direction of sustainability assessments. This book will be extremely useful to both researchers and practitioners who are looking for best--in-class practices to create value from their sustainability initiatives." --